Modulating glutathione thiol status alters pancreatic β-cell morphogenesis in the developing zebrafish (Danio rerio) embryo - Rastogi, Archit (Redox Biol, 2020)
Emerging evidence suggests that redox-active chemicals perturb pancreatic islet development. To better understand potential mechanisms for this, we used zebrafish (Danio rerio) embryos to investigate roles of glutathione (GSH; predominant cellular redox buffer) and the transcription factor Nrf2a (Nfe2l2a; zebrafish Nrf2 co-ortholog) in islet morphogenesis. We delineated critical windows of susceptibility to redox disruption of β-cell morphogenesis, interrogating embryos at 24, 48 and 72 h post fertilization (hpf) and visualized Nrf2a expression in the pancreas using whole-mount immunohistochemistry at 96 hpf. Chemical GSH modulation at 48 hpf induced significant islet morphology changes at 96 hpf. Pro-oxidant exposures to tert-butylhydroperoxide (77.6 μM; 10-min at 48 hpf) or tert-butylhydroquinone (1 μM; 48-56 hpf) decreased β-cell cluster area at 96 hpf. Conversely, exposures to antioxidant N-acetylcysteine (bolsters GSH pools; 100 μM; 48-72 hpf) or sulforaphane (activates Nrf2a; 20 μM; 48-72 hpf) significantly increased islet areas. Nrf2a was also stabilized in β-cells: 10-min exposures to 77.6 μM tert-butylhydroperoxide significantly increased Nrf2a protein compared to control islet cells that largely lack stabilized Nrf2a; 10-min exposures to higher (776 μM) tert-butylhydroperoxide concentration stabilized Nrf2a throughout the pancreas. Using biotinylated-GSH to visualize in situ protein glutathionylation, islet cells displayed high protein glutathionylation, indicating oxidized GSH pools. The 10-min high (776 μM) tert-butylhydroperoxide exposure (induced Nrf2a globally) decreased global protein glutathionylation at 96 hpf. Mutant fish expressing inactive Nrf2a were protected against tert-butylhydroperoxide-induced abnormal islet morphology. Our data indicate that disrupted redox homeostasis and Nrf2a stabilization during pancreatic β-cell development impact morphogenesis, with implications for disease states at later life stages. Our work identifies a potential molecular target (Nrf2) that mediates abnormal β-cell morphology in response to redox disruptions. Moreover, our findings imply that developmental exposure to exogenous stressors at distinct windows of susceptibility could diminish the reserve redox capacity of β-cells, rendering them vulnerable to later-life stresses and disease.